2018
DOI: 10.1001/jamaoncol.2018.0211
|View full text |Cite|
|
Sign up to set email alerts
|

Hormone Replacement Therapy After Oophorectomy and Breast Cancer Risk Among BRCA1 Mutation Carriers

Abstract: These findings suggest that use of estrogen after oophorectomy does not increase the risk of breast cancer among women with a BRCA1 mutation and should reassure BRCA1 mutation carriers considering preventive surgery that HRT is safe. The possible adverse effect of progesterone-containing HRT warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 42 publications
4
113
0
4
Order By: Relevance
“…Another study, which spanned 7.6 years, showed that there was no increased risk in future breast cancer development in BRCA1 carriers, post‐oophorectomy, who were using HRT compared to non‐users. This further confirms that estrogen replacement does not increase the risk of breast cancer, even among high‐risk populations …”
Section: Safety Of Hormone Replacementsupporting
confidence: 72%
“…Another study, which spanned 7.6 years, showed that there was no increased risk in future breast cancer development in BRCA1 carriers, post‐oophorectomy, who were using HRT compared to non‐users. This further confirms that estrogen replacement does not increase the risk of breast cancer, even among high‐risk populations …”
Section: Safety Of Hormone Replacementsupporting
confidence: 72%
“…The use of estrogen-only MHT appeared protective in women with a previous hysterectomy; with a notable, but not statistically significant, 8% reduction in breast cancer per year of use. 138 These findings are consistent with the overall reduction in breast cancer seen in the estrogen-only arm of the WHI; in addition, they may sway patients and providers toward consideration of hysterectomy at the time of RRSO to allow for estrogen-only MHT postoperatively.…”
Section: The Role Of Mht In Women At Risk Of Developing Breast and Ovsupporting
confidence: 68%
“…The strength of this study is its prospective design. Many of the biases identified in previous reports were addressed [7,9,17,18]. We avoided cancer testing-induced bias by starting follow-up after mutation testing.…”
Section: Discussionmentioning
confidence: 99%